Cross-Selling Customer Service Strategy in Increasing Product Sales - Triana, Nanda; Ahmadi Bi Rahmani, Nur; Amin Dalimunte, Ahmad (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to find out how the cross-selling strategy is carried out by customer service in selling products at PT. Bank Muamalat KCU Medan Balaikota and find out what obstacles customer service faces so that it does not reach targets. This research uses a qualitative descriptive research type. The methods used are SWOT and QSPM. The problem faced by customer service in carrying out cross-selling is the condition of the customer and the customer already having a product at another bank. The results of this research show that the current state of the internal and external environment is increasing cross-selling customer service, namely: a. Product strengths are Health, education, and Hajj insurance products that comply with Sharia, various savings products according to customer needs. M-banking is safe and secure, the features in m-banking can meet customer transaction needs and Hajj/multipurpose financing products are trusted and easy for the public to apply for b. Current weaknesses: Few service offices and customers who are still considering accessing Bank Muamalat services make customers experience difficulties. Current opportunities: Adding to the company’s image with excellent service so that it can create a customer experience. The main priority strategy that must be implemented at PT. Bank Muamalat KCU Medan Balaikota is developing cross-selling strategy techniques to increase product sales and create customer experience.